The Determinants of Innovation in Malaysian Food Processing Small and Medium Enterprises (SMEs) - Suziyana, Mat Dahan; Ahmad Nazif, Noor Kamar; Rabiatul Syuhada, H.; Nurhaizan, Mohd Zainudin; Fadzida, Ismail (Elsevier, 2015)
Innovativeness of a new product and Small and Medium Enterprise (SME) innovation capability is important to present opportunities for SMEs in terms of growth and expansion into new areas as well as allow SMEs to gain competitive advantage. Realising the essential contribution of food processing SMEs towards Malaysia’ economic growth, various incentives and assistance formulated by government to stimulate them to become more aggressive in undertaking innovative activities. Such innovation initiatives are driven by various factors such as changes in consumers’ preferences, technological change, research and development activities, skills of workforce and many more. This paper discusses the innovation successfulness among food processing SMEs in Pahang, Malaysia. It aims to study the factors which determine innovation activities in food processing SMEs and which of them are the most influencing one. The key factors studied were identified as firm culture, firm innovation management, experience with innovation, appropriate resources allocation, and freedom to innovate. The respondents involved were 85 SME’s owner, who had been approached through survey. By using Statistical Package for the Social Sciences (SPSS), the result obtained by finding the mean value for each of the item assessed. Results revealed that the appropriate resources allocation is the most influencing determinants of innovation successfulness among food processing SMEs. Two main firm’s resources; time and money found to be the major aspect in business field which needs to be managed systematically and properly. The findings are mainly benefited the SMEs owners and related government agencies in restructuring the strategies towards more efficient innovation adoption and implementation.